Recognition and presentation of real estate projects costs – key problems - Jacek Kalinowski (Zeszyty Teoretyczne Rachunkowości)
The aim of the paper is to present the main problems of recording, settlement and presentation of costs in real estate projects. The following issues are explained: ● beginning of a real estate project ● recognition of land or the right of perpetual usufruct of land in real estate projects ● reclassification of recognition and presentation of a real estate project after its completion. In order to accomplish the purpose of the article, a critical analysis of available literature and selected accounting regulations, both Polish and internation-al, was carried out. In addition, case studies were used to better illustrate the problems. The presented examples and their explanations should be taken as guidelines to the interpretation of various provisions of accounting regulations. In particular, they are an extension of the content of Domestic Accounting Standard no. 8 Real estate projects. Since the role of accounting is to depict the economic reality in such a way as to make information useful to a wide audience, the problems raised in this article are intended to approximate us to this ideal goal, which is provision of credible, reliable, useful and timely information.